The books of Ezra and Nehemiah with introduction, notes and maps - Ryle, Herbert Edward, 1856-1925 (Cambridge, UK Cambridge UP, 1893)
Includes bibliographical references and index.
1901 reprint. Author is son of J.C. (John Charles) Ryle.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries